Gambaran Anak Dengan Gangguan Spektrum Autisme Di Wilayah Indonesia Periode Tahun 2017 Sampai Dengan 2020 - Deva, Marchelie Putri Tuice; Rauf, Darmawati; Suwono, Veronika (Fakultas Kedokteran Universitas Bosowa, 2025)
Autism spectrum disorder is a neurodevelopmental developmental disorder characterized by decreased function in reciprocal social interaction abilities, communication and language deficits, stereotyped behavior, limited interests and activities. The purpose of this study was to determine the description of children with autism spectrum disorders using a descriptive method with a synthesis approach of several research articles. The research used is ten studies from various research sites in Indonesia. The results showed that from 10 studies, the most cases were diagnosed at pre-school age with an incidence of 94 cases with a percentage of 66.67%, males were more reported to suffer from autism spectrum disorders with an incidence rate of 147 cases with a percentage of 78.6%, normal birth weight was more Many experienced autism spectrum disorders, namely 143 cases with a percentage of 66.82% and had a history of pregnancy complications in 268 cases with a percentage of 57.47%, middle to upper socioeconomic status as many as 41 cases with a percentage of 68.3%. The conclusion is that the prevalence of children with autism spectrum disorders is more diagnosed at pre-school age, more in boys, with normal birth weight, and who have a history of pregnancy complications, as well as upper middle socioeconomic status.